An Analysis of Implicature in Drew Lynch's Stand-Up Comedy - Farkhan Sholakhudin; Muhammad Burhanuddin; Irma Khoirot Daulay; Toyyibah Toyyibah (Universitas Muria Kudus, 2025)
Misunderstandings often arise in stand-up comedy, leading to varied audience reactions. Since individuals come from diverse knowledge backgrounds, they must grasp the implicit meanings to fully understand the context of a comedian's speech. However, not all audience members can successfully interpret the context of the jokes. In stand-up comedy, comedians frequently violate the maxims of Grice's (1975) cooperative principle, which creates humor through implicature. This study focuses on analyzing the types and uses of implicature in Drew Lynch's American stand-up comedy performances. Using Grice's (1975) implicature theory, the research employs a descriptive qualitative method, with data collected by listening to and transcribing performances to examine discourse aspects. The findings reveal how Drew Lynch uses implicature to share his opinions, experiences, and emotions humorously, making it easier for the audience to connect with his material. Additionally, the study highlights Lynch's use of lexical items, categorized as references, inferences, and presuppositions, to aid audience comprehension. The study encourages future researchers to delve into other dimensions of implicature, such as its social aspects, or explore its application in different mediums like movies or comics.